Metode Dakwah Abdul Hayyi Somad - Achmad Yaman; Syarifuddin Syarifuddin (STID DI AL-HIKMAH, 2017)
The purpose of this study was to determine the method used dakwah Hayyi Abdul Somad at Ash-Shifa Taklim Assembly. The researchers carried out using descriptive qualitative approach. The research data obtained through reference in reading, observation, interviews and documentation. The main data sources were collected through direct observation in the field and engage directly with mad'u who follow the activities of proselytizing. Conclusion of the study is a method of dakwah used Hayyi Abdul Somad, exemplary methods of dakwah by the deed that is real, that is to say a scholar first provide role models (uswah) good to the congregation. This is in line with the expression lisanu al-case afshohu min lisani al-maqal (preaching to the action better than with words). Mujadalah method or a brainstorming debate conducted by the two parties in a synergistic and not cause hostility.